Energy efficiency and energy pre-diagnostic in education institutions of João Monlevade - MG (Research, Society and Development, 2019)
This paper aims to disseminate knowledge about energy efficiency to students of educational institutions in the municipality of João Monlevade in the state of Minas Gerais. Thus, the project aimed to propagate educational practices related to the efficient use of electric energy, combating energy wastage and consequently promoting the conservation of natural resources and reducing the impact of the cost of energy on the family budget of participants and schools. . Thus, the project was developed with approximately 144 children, from the first to fifth year of elementary school, who were approached through playful games. During this process, an energy pre-diagnosis was performed in one of the partner schools, in order to present the main errors regarding energy use and to suggest effective and simple actions to minimize them. . In addition, through research conducted at the beginning and end of the project with the participants, it was possible to verify that the promotion of the activities corresponded satisfactorily to the objectives of the project, since before the execution only 6% of the students were aware of the subject, increasing to 86% after the promotion. In this way, it is concluded that, the development of projects of this type contributes in the formation of agents promoting the fight against the waste of electric energy. All this, through simple actions that promote the conservation of electric energy without reducing the quality of life. It is also emphasized that this type of proposal also serves as support and motivation in the search for knowledge and socioeconomic and sustainable development of the country.